The role of government - (2) - Tatad, Francisco S. (Philippine Journal of Public Administration, 1986)
The Aquino government must contend with competing new forces in addition to societal groups that are permanently hostile to any government that is not their own. In order to effectively govern, the government must maintain a decisive dominance over these forces. The following are necessary: (1) a solid party structure; (2) monopoly of the state on the use of arms; (3) harmonious relationship with the Church without compromising the separation between these two institutions; and (4) government as a partner instead of competitor to private business.